An Observational Study on the Association between Migraines and Tension Type Headaches in Patients Diagnosed with Metabolic Syndrome. (18th April 2013) - Gozke, Eren; Unal, Muge; Engin, Hayriye; Gurbuzer, Nurbanu
Abstract : Background . Our aim was to investigate the association between migraine, tension type headache, and metabolic syndrome. Methods . Presence of tension type headache and migraine was investigated in 120 patients diagnosed as metabolic syndrome. The severity of the headache was recorded according to the visual analog scale. Results . Mean age of the patients was 54.41 ± 11.60 years (range, 29–84 yrs). Diagnoses of tension type headache and migraine without aura were made for 39 (32.5%) and 18 (15%) patients, respectively. Mean age of migraine patients was significantly lower relative to the patients with tension type headache and no headache. Incidence of hypertriglyceridemia was significantly higher in migraine patients when compared with cases tension type headache and without headache. In the tension type headache group, requirement for analgesics decreased as HDL cholesterol levels increased, while need for analgesic drugs increased in line with higher diastolic blood pressures. In the migraine group duration of headache was found to be prolonged with decreasing HDL cholesterol levels. Conclusion . In patients presenting with headache, its association with metabolic syndrome should be considered, and the patients should be especially observed with respect to response to analgesic and the presence of hypertension and hyperlipidemia.